Preparation and characterization of cellulose-based nanoparticlers and hydrogel - Su, Shei Sia (Universiti Malaysia Sarawak, UNIMAS, 2007)
This project focuses on the synthesis and characterization of cellulose-based nanoparticles and hydrogel from three different sources. Preparation and modification of cellulose particles size required the dissolution of cellulose in suitable solvent systems. Two solvent systems, a solution mixture of 6% NaOH and 5% Thiourea, a 8.5% NaOH solution were used in the dissolution of cellulose samples. Differences in cellulose solubility for these two solvents systems were compared and changes in chemical structures of cellulose were characterized. Three main cellulose-based particles were prepared: regenerated cellulose, cross-linked cellulose and cellulose nanocrystallite. Regenerated celluloses were prepared by dialysis of cellulose suspensions against ultra-pure water for different time intervals. The regenerated cellulose appeared to form aggregation readily with increase in the dialysis duration. Meanwhile, cross-linked cellulose particles were synthesized in the water-in-oil emulsion using epichlorohydrin (ECH) as the cross-linker. Cellulose nanocrystallites were prepared by sulfuric acid hydrolysis. Preparation of cellulose nanocrystallites was strongly dependent on hydrolysis temperature and time. The particles sizes, morphology and chemical structures of these cellulose-based particles were characterized by SEM and FTIR. Though particles synthesized from different sources possessed very similar physical and chemical properties, they are distinctively different morphologically from their respective precursor materials.